Rat adipose-derived mesenchymal stem cell-derived exosomes loaded with miR-375 promote neurite outgrowth and peripheral nerve regeneration via activation of Akt by targeting EPHA4 - Zhiwei Liu; Yuanyuan Han; Chunjie Song (Regenerative Therapy, 2025)
Background: MicroRNAs (miRNAs) carried by mesenchymal stem cells (MSCs)-derived exosomes participate in peripheral nerve regeneration. Our study intended to determine the role of miR-375-loaded exosomes secreted by adipose-derived MSCs (ADMSCs) in dorsal root ganglion (DRG) neurons in vitro and in rat models of sciatic nerve injury as well as the underlying mechanisms. Methods: After the isolation of primary rat ADMSCs and DRG neurons, the characteristics of ADMSC-derived exosomes were identified by western blotting and nanoparticle tracking analysis. MiR-375 mimics or NC mimics were transfected into ADMSCs to prepare exo-miR-375 or exo-NC. Then, DRG neurons were co-cultured with exo-miR-375 or exo-NC to analyze the influence of exosomes loaded with miR-375 on axon extension by neurofilament immunofluorescence staining and neurotrophic factor production by RT-qPCR. A walking track analysis was conducted to assess the effects of exo-miR-375 or exo-NC injection on the recovery of rat sciatic nerve functions. Axon and myelinated fiber regeneration in injured nerves was observed through toluidine blue staining, transmission electron microscopy (TEM), and neurofilament immunofluorescence staining. TargetScan and miRDB databases were used to screen for miR-375 downstream target genes. The miR-375 and EPHA4 interaction relationship was validated through dual luciferase reporter assay. The phosphorylation of Akt in sciatic nerve tissues was determined via western blotting. Results: ADMSCs-derived exosomes with overexpressed miR-375 stimulated axon extension and enhanced neurotrophic factor expression in DRG neurons as well as improved limb function recovery, facilitated axon myelinated fiber regeneration, and alleviated gastrocnemius muscle atrophy in rats after sciatic nerve injury. EPHA4 targeted by miR-375. Overexpressing EPHA4 reversed the promotion of exo-miR-375 on neurite outgrowth in vitro. Additionally, exo-miR-375 significantly reduced EPHA4 levels but elevated phosphorylated-Akt levels in rat sciatic nerves. Conclusion: ADMSCs-derived exosomes with overexpressed miR-375 promoted neurite outgrowth and peripheral nerve regeneration by activating Akt through downregulating EPHA4.